A determination of the value of the concepts of the Covenant and the People of God, derived from representative contemporary Jewish, Protestant, and Catholic theologians as a basis for ecumenical dialogue and agreement - Kelly, William Doane (University of Ottawa (Canada), 1964)
Abstract not available.
Keywords: Religion, General.; Religion, Comparative.